Chapeau! First-Year French - Dinneen, David A.; Kernen, Madeleine (Open textbook library., 1989)
Chapeau! is a first-year college text. Although it may appear, at first glance, to move very fast and introduce a large amount of material early, the vocabulary and grammatical structures that we expect students to control actively by the end of the year are limited in accord with our notion of a reasonable application of the ACTFL proficiency guidelines. As a result, while some instructors may be surprised at such things as the absence of the possessive pronoun, no insistence on the use of optional subjunctives, and no active treatment of the relative dont, others may be disturbed by what we still include in a first-year text. What we do expect students to acquire (which is quantitatively less than what we present in the text for them to know about), we believe they will acquire well, providing a sound basis for further study (formal or informal) and permitting us to say to them, both during and at the end of the course, "Chapeau!"